O humanismo personalista de Emmanuel Mounier e a repercussão no Brasil - Silveira, Carlos Roberto da (2010)
The personalism of Emmanuel Mounier (1905-1950) came up during a historical situation permeated by great disorder. Within the context of mankind in crisis, Mounier always promoted the person. He defended the recovery of inalienable human rights, and paved the way for the ethical universe of the person in his time and place. He proposed an awakening, a bloom of the true human existence made of immanence and transcendence. Thus awakened, the person, being-in-the-world and with-the-world, takes hold of his humanity, refuses passivity and conformism when faced with alienating threats of any nature. His philosophy, which unites reflection and action, reached the other shores of the Atlantic and had an improving repercussion in Brazil from the fifity s. Times of great intellectual, cultural, philosophical, political, and social production were lived as never before in the history of Brazil. Everything was interrupted by the Military Coup of 1964: came to an end the spring of the times for liberty, education and a culture centralized in the dignity of the human person. Not following the logic of the seasons, it was starting a long time of somber winter. A time that can be never forgotten, even though nowadays everything is being done to reject this shamefull past. Anyway, even under the iron fist of the totalitarian order (established disorder), the personalism in Brazil during the 1970 s managed to maintain the spark lighted through a starting trench of thinking, specifically more philosophical. Time going, attending to nowadays time, it is noticed that new incidents against human dignity do occur daily. It is not an odd thing to think that, referring at the beginning of the 21st century to the view uphold by Mounier, one comes to rediscover that the idea of the person can contribute much to our time. Mounier s thought about the person can provide help for a personal awakening that enclose each other, promoting a responsibility ethics , and bringing with it, in the structures of its personal universe, something new, so much needed by a community (commonunity), that urgently must be understood as planetary